The Mosque Committee Conflict: An Ethnographic Study - Ummi Sa’adah; Muhammad Isa; Indah Masruroh (Indonesian Journal of Da'wah Management Scholars, 2025)
Purpose – This study examines the factors causing conflict within a religious institution, in this case, a mosque, and the reconciliation process. Design/methodology/approach – The ethnographic approach was employed as a qualitative research method due to the protracted and intricate nature of the conflict phase at Nasrullah Mosque in Bengkulu City, Indonesia. The data collection process was initiated in 2022, with the intensive phase of interviews taking place from June to December 2024. Findings – Poor financial transparency was identified as the underlying cause of the problems that arose at Nasrullah Mosque. The failure of mosque administrators to furnish financial reports resulted in the manipulation of the mechanism for replacing mosque leaders. Ethnic issues and differences in religious practices were used to remove several leaders who were critical of the accountability of mosque funds. Research implications – The findings of this study are of particular utility to practitioners and mosque administrators, as they underscore the necessity for enhanced transparency, accountability, and effective communication in the resolution of conflicts. Originality/value – Disputes over mosque management rights are seldom documented in an ethnographic context. A substantial body of research has previously focused on conflicts between mosques and their surrounding communities. Paper type - Research paper